Graffiti, street art, murals and music - Rasimi, Adhurim H.; Mazreku, Faton (Street Art & Urban Creativity, 2023)
This research analyzes graffiti and murals made by young artists who are school students in Kosovo, and some of the professional artists, as a visual expressive description for certain purposes. Murals and graffiti which are made by students differ from those by professional artists in the field of visual arts, for the fact that naturally the graffiti made on the internal and external walls of schools display superficial and educational messages but still show creative aspects of the feeling for mural painting. A part of the graffiti were interwoven with musical art and represent the influence or inspiration from various musical components which in their images show musical content in the representation such as: musical instruments, musical performers, musical genres, musical bands (orchestras), and various musical symbols, notes, staff (pentagrams), musical keys, etc. The graffiti made by the students show their peculiarities in the content and in their messages. They are numerous in some schools in Kosovo, where graffiti fulfills the need of students to enforce any given topic, either social or educational. The importance and peculiarity of this research is that it highlights that the creation of graffiti-murals by students of different ages contains and displays empowering messages on certain topics, although art can also be used in other mediums where they convey their messages, however, in the murals there lies a greater power for conveying a message.